ANALISIS NILAI ETIKA TOLONG-MENOLONG TOKOH HEPI DALAM NOVEL ANAK RANTAU KARYA A. FUADI - Selfi Maikomah; Erlina Zahar; Harbeng Masni (Universitas Batanghari Jambi, 2018)
Abstract: The purpose of this study is to describe the ethical value of the help of the Hepi character in Son Rantau novel by A. Fuadi. This research includes descriptive research type which is qualitative. Primary data in this research is in the form of written data in the form of sentences, words, and paragraphs in the form of dialogs and monologues contained in Hepi characters in novels Anak Rantau A. Fuadi, while secondary data in this study in the form of books and literature taken from the library where the theories relate to this research. Based on the results of this study it can be concluded that the value of the helpful ethics contained in the novel Rantau Son of A. Fuadi there are 24 quotations are all reinforced also by exposure to dialogue and monologue. This illustrates this novel put forward that people live in society is needed each other to help each other in order to create prosperity help-help is necessary in living life because human life must be socialized and interdependent with each other Keywords: Value, ethics, novel